"Cos You're Quite Normal, Aren't You?": Epistemic and Deontic Orientations in the Presentation of Model of Care Talk in Antenatal Consultations. Issue 3 (23rd February 2021) - Cole, Lindsay; LeCouteur, Amanda; Feo, Rebecca; Dahlen, Hannah
ABSTRACT: Women's involvement in decision-making around antenatal care is an issue of ongoing debate and discussion. Most research on the topic has used interview and focus group methods to examine women's perspectives. The present study uses a different kind of evidence. By analyzing recordings of actual antenatal consultations, this paper presents a preliminary exploration of model-of-care talk in a hospital setting where a policy of woman-centered care underpinned practice. Conversation Analysis was used to examine how model-of-care pathways were introduced by midwives and discussed with women in consultations. Drawing on interactional work on deontic (i.e., the rights and responsibilities of speakers to determine courses of action) and epistemic (i.e., speakers' claims to knowledge) orientations, this paper offers an account of how woman-centered care is accomplished in a hospital setting. The findings demonstrate how midwives routinely relied on their epistemic knowledge regarding women's health to invoke a "normal" categorization that worked to position midwifery-led care as an appropriate pathway. Examination of model-of-care talk also demonstrated how authority to choose a pathway was typically managed so as to reside with the woman. Talk that topicalized epidural forms of pain management were also examined, as institutional policy around where birth could occur in the hospital system under study restricted women's options (a planned epidural precluded woman access to midwifery-led care during delivery). The findings demonstrate the various ways in which midwives created opportunities for woman-centered care in an institutional setting in which there were logistical restrictions on women's choices.